Chemical synthesis of cyclotide from the medicinal plant clitoria ternatea - Wang, Yingqi (2013)
Cyclotides are a special class of ultrastable peptides which possess a cyclized backbone and three disulfide bridges. They display many bioactivities and are attractive targets for drug discovery. The medicinal plant Clitoria ternatea contains a high abundance cyclotides, named as cliotides (cT, which have been shown to constitute the active ingredients of C. ternatea. cT19 is one of the cliotides that showed strong antibacterial and immunomodulatory activities. Native cT19 yield from conventional extracting methods is relatively low and it is difficult to separate cT19 from its deaminated form cT19a. With the recent understanding of cT19’s structure and amino acid sequence, chemical synthesis of cT19 is made possible. [2nd Award]